New Structural Patterns in Moribund Grammar: Case Marking in Heritage German - Yager, Lisa; Hellmold, Nora; Joo, Hyoun-A; Putnam, Michael T.; Rossi, Eleonora; Stafford, Catherine; Salmons, Joseph (Frontiers in Psychology, 2015)
Research treats divergences between monolingual and heritage grammars in terms of performance—‘L1 attrition,’ e.g., lexical retrieval—or competence—‘incomplete acquisition’, e.g., lack of overt tense markers (e.g., Polinsky, 1995; Sorace, 2004; Montrul, 2008; Schmid, 2010). One classic difference between monolingual and Heritage German is reduction in morphological case in the latter, especially loss of dative marking. Our evidence from several Heritage German varieties suggests that speakers have not merely lost case, but rather developed innovative structures to mark it. More specifically, Heritage German speakers produce dative forms in line with established patterns of Differential Object Marking (Bossong, 1985, 1991; Aissen, 2003), suggesting a reallocated mapping of case. We take this as evidence for innovative reanalysis in heritage grammars (Putnam and Sánchez, 2013). Following Kamp and Reyle (1993) and Wechsler (2011, 2014), the dative adopts a more indexical discourse function, forging a tighter connection between morphosyntax and semantic properties. Moribund grammars deploy linguistic resources in novel ways, a finding which can help move us beyond simple narratives of ‘attrition’ and ‘incomplete acquisition.’